Evaluation of different Terminalia chebula varieties and development of functional muffins - Khalil, Ejaz; Sultan, Muhammad Tauseef; Khalid, Waseem; Khalid, Muhammad Zubair; Rahim, Muhammad Abdul; Saleem, Samavia Rashid; Luca, Marian-Ilie; Mironeasa, Costel; Batariuc, Ana; Ungureanu-Iuga, Mădălina; Coţovanu, Ionica; Mironeasa, Silvia (Frontiers in Sustainable Food Systems, 2023)
Terminalia chebula is a valuable medicinal plant that can be used in human nutrition. The current study was conducted on different varieties of Terminalia chebula (Harad) and aimed to investigate their proximate composition, antioxidant activity (DPPH and FRAP assay), and total phenolic content (TPC) by using different solvents (ethanol, acetone, hexane, and distilled water) for further use in the development of functional muffins. Wheat flour was supplemented with the Harad varieties (at 5%, 7.5%, 10%, or 15%) for the preparation of muffins. The color tonality (L*, a*, b*, C*, and h*) of the final product was measured with a digital colorimeter, and the sensory analysis was performed by using a 15-point scale. The results showed that the DPPH values of the Harad samples varied from 22.16 ± 1.27 to 84.33 ± 1.29, while the FRAP values ranged from 18.65 ± 1.73 to 113.4 ± 2.1 mmol FeSO4/g, depending on the solvent type. TPC in different Harad varieties ranged from 10.77 ± 2.35 to 107.20 ± 1.80 mg GAE/100 g, whereas the total flavonoid content ranged from 3.78 ± 0.03 to 47.91 mg QE/100g. Among Harad varieties, the Kabuli variety contains the highest amount of Ca, Na, and K, namely 95.58, 2.16, and 113.66 mg/kg, followed by the black variety with 89.58, 1.83, and 105.08 mg/kg respectively. The muffins prepared with black Harad give the highest values of the color parameters compared to other samples. According to the consumer’s choice, the sensory profile assessment revealed that the muffins supplemented with 7.5% of different Harad varieties (green, black, and Kabuli) were the most acceptable. Therefore, Harad varieties could partially replace the white flour in muffins to improve their nutritional value. These results can be useful for the bakery industry interested in developing new functional foods.